Less Is More: A Vision Rethought for the 21st Century - Beat Kämpfen (Oz, 2013)
“Less is more”—Ludwig Mies van der Rohe’s famous statement—defined the paradigm with the largest influence on design of our cities and architecture over the second half of the last century. During this period, the main public interest in architecture was to be found in rapidly increasing the speed of production while at the same time lowering construction costs.